Níveis de Landau-Coriolis - Silva, Júlio Eloísio Brandão da (2013)
Inertial effects, such as Coriolis’ and centrifuge forces play an interesting role on classical mechanics and currently has been largely used in quantum mechanics, including in analogies with the electromagnetic effects. However, these analogies between the inertial forces on the massives particules and the electromagnetic forces on charged particles is not new. They were explored by Aharonov and Carmi in 1970 and by Tsai and Nelson in 1988 in the context of a rotational quantum phase like an Aharonov-Bohm phase. Based in this analogy, Dattoli and Quattromini, introduced Coriolis’ analogue quantum states to Landau levels. In 1915, Barnett had already published a paper about magnetization due to rotation which recently had a renewed interest applyed to nanostructures. A rotational analogy of the classical Hall effect was proposed and rotational inertial forces were studied in spintronic. Energy spectra like Landau levels appear under the action of Coriolis forces when the centrifuge force acting on free electrons is compensated by a radial electric field. In this work, we will demonstrate effects caused by rotation and magnetic field in a spinning conductor disc. We will study both the electromagnetic and inertial interactions simultaneously. Some values to the relation between the magnetic field and the rotation will be chosen and this will result in Landau-like levels to a system with resultant force composed by Coriolis’ and magnetic forces. A similar behavior for the energy spectrum will be found without a magnetic force composing the resultant force.